Restitution of Children Victims f Sexual Crime - Ratna Pertiwi (Pancasila and Law Review, 2020)
Indonesia as a constitutional state and has a state foundation, namely Pancasila, which is the basis for various countries in determining policies for the state. Protection of children as the nation's next generation should be improved considering that in the current era there are more and more cases of violence, sexual harassment, and other crimes that make children the object of violence itself. One form of prevention is by issuing policies in the form of laws and regulations that provide strict sanctions against the perpetrators. This study uses a Normative and Empirical Juridical approach. The normative approach is carried out on matters that are theoretical in legal principles, while the empirical approach is an attempt to obtain clarity and understanding of research problems based on existing realities or case studies. The results of the research obtained related to the implementation of the restitution rights of children victims of sexual crimes must go through 3 stages, namely the first, the formulation stages have been carried out properly with the passing of PP No.43 of 2017. The second stage of application has not been carried out optimally because many law enforcement officers do not understand Regarding the implementation of restitution and the limitation on the economic capacity of the perpetrator to pay restitution, it is also an obstacle in its execution. The three stages of execution are maximal because the execution by the prosecutor has been carried out after the decision has permanent legal force (incracht). The implication can be seen from the victim's point of view that their rights are fulfilled from the existence of this policy. The suggestions that can be conveyed in this research are that the restitution execution process should be regulated as well as the execution of replacement money in a Corruption Crime Case. So if the perpetrator who is determined to pay restitution does not want to voluntarily pay the restitution, the prosecutor's office can find assets owned by the perpetrator to be confiscated instead.